2018
DOI: 10.3390/colloids2010005
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Surface Tension Measurements for Animal Blood Analysis and Correlations with Related Biochemical Parameters

Abstract: Abstract:The dynamic surface tension (DST) data and biochemical parameters (BCP) of animal blood have been obtained. A strong positive correlation was found for goats between σ 1 , σ 2 , σ 3 (DST) and sodium levels (BCP), λ z (DST)-with the levels of lipid and sodium (BCP); whereas a strong negative correlation was found for goats between σ 3 (DST) and the level of total protein and chloride (BCP), λ z (DST)-with the level of albumin (BCP). A strong positive correlation was found for horses between σ 1 , σ 2 ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Comparison of the data obtained by BPA-1P with those by other well-known methods (oscillating jet, drop volume, dynamic, capillary, etc.) (Miller & Fainerman, 1998;Kazakov et al, 2000;Khilko, 2014;Voronina, 2017;Zaitsev et al, 2004Zaitsev et al, , 2011bZaitsev, 2016Zaitsev, , 2018 showed a good agreement between the results.…”
Section: Dynamic Tensiometry Analysismentioning
confidence: 85%
See 3 more Smart Citations
“…Comparison of the data obtained by BPA-1P with those by other well-known methods (oscillating jet, drop volume, dynamic, capillary, etc.) (Miller & Fainerman, 1998;Kazakov et al, 2000;Khilko, 2014;Voronina, 2017;Zaitsev et al, 2004Zaitsev et al, , 2011bZaitsev, 2016Zaitsev, , 2018 showed a good agreement between the results.…”
Section: Dynamic Tensiometry Analysismentioning
confidence: 85%
“…The dependance of the dynamic surface tension parameters (Zaitsev, 2016) of the serum on the qualitative and quantitative composition has been described (Zarudnaya et al, 2010;Zaitsev et al, 2011b;Zaitsev, 2010Zaitsev, , 2018. The dependance of the DT parameters (complete quantitative data set) of the serum of some animals (Fig.…”
Section: Dynamic Tensiometry Parameters Of Cattle Serummentioning
confidence: 95%
See 2 more Smart Citations